A Comparative Study of Soiling on Solar Mirrors in Portugal and Morocco: Preliminary Results for the Dry Season - Conceição, Ricardo (2019)
Soiling is a factor of major importance regarding any solar energy conversion technology, as in Photovoltaic (PV) panels and, namely, in concentrated solar power (CSP), since scattering due to particle deposition severely reduces the mirror’s reflectance. Concerned with this problem, a collaboration between the Renewable Energies Chair, University of Évora, Portugal and the Institut de Recherche en Energie Solaire et Energies Nouvelles, Morocco, was created to investigate and compare soiling in mirrors in both locations. This research enables the comparison between particle deposition effects in the two climates, crucial to implement mitigation measures. Southern Portugal and Northern Africa have considerable potential for future CSP installations, which makes this study relevant from an economical point of view, as it may influence the maintenance procedures and expected energy production of such CSP plants.